Endoscopic Submucosal Dissection for Treatment of Patients Aged 75 Years and over with Esophageal Cancer. (17th June 2012) - Kikuchi, Osamu; Mouri, Hirokazu; Matsueda, Kazuhiro; Yamamoto, Hiroshi
Abstract : Background . Although many reports concerning the use of endoscopic submucosal dissection (ESD) for esophageal cancer have been published, the feasibility of ESD in elderly patients has not been reported. Therefore, we evaluated the efficacy and safety of ESD for treating early esophageal cancer in elderly patients. Methods . A total of 62 cases (52 men, 10 women; mean age ± standard deviation, 66.5 ± 10.5 years) for which the first resection (first treatment) of esophageal cancer was performed by ESD were identified from 77 consecutive esophageal epithelial cancers in 67 patients treated at our institution from January 2005 to March 2011. Patient characteristics, clinical findings, and outcomes were retrospectively assessed for patients separated into older (aged 75 years and older) and younger (aged under 75 years) groups. Results . No significant differences in specimen size, procedure time, median length of the hospital stay (8 versus 9 days; P = 0.252 ) or procedure-associated complications (8% versus 27%; P = 0.264 ) were observed between the older (n = 13 ) and younger (n = 49 ) groups. Lesions were completely resected in 12 patients and 44 patients, in the younger and older groups, respectively, and the curative resection rate was 77% and 59%, respectively. There were no deaths attributable to procedure-associated complications. Conclusions . ESD is an effective treatment for early esophageal cancer and is well tolerated by elderly patients.